Alexithymia – State or Trait? - Ortiz-soria, Beatriz; Martínez-sánchez, Francisco; Ato-garcía, Manuel (The Spanish Journal of Psychology, 2003)
Alexithymia refers to a specific disturbance in emotional processing that is manifestad by difficulties in identifying and verbalizing feelings and a tendency to focus on and amplify the somatic sensations that accompany emotional arousal. Alexithymia is conceptualized both as an affect-deficit disorder and a continuous personality variable. The main purpose of the present study was to investigate the stability levels of alexithymia with regard to changes in emotional distress levels caused by university exams. We tested 20 university students at four different times, before and after the exams. Alexithymic features and self-reported emotional distress (trait anxiety and physical symptoms) were measured. Whereas emotional distress measures changed significantly during the diverse phases, the level of alexithymia remained unchanged. We therefore conclude that alexithymia represents a constant trait
Keywords: emoción; alexitimia; estrés; ansiedad